Determining factors for dexmedetomidine sedation in endoscopic submucosal dissection for early‐stage gastric cancer - Erika Yoshida; Yorimasa Yamamoto; Misako Tohata; Kuniyo Gomi; Tadashi Okayasu; Masatsugu Nagahama (JGH Open, 2024)
Abstract Background and Aim Although no specific sedation recommendations exist in early‐stage gastric cancer (ESGC) for endoscopic submucosal dissection (ESD), dexmedetomidine (DEX) is useful along with benzodiazepines and analgesics. Furthermore, DEX is used for endoscopic treatment requiring lengthy sedation. However, it is unclear which patients should be administered DEX. We examined the factors that determine when DEX should be added for sedation during ESD for ESGC. Methods Of 316 patients undergoing ESD for ESGC at our hospital between January 2017 and December 2020, we examined 310 receiving intravenous anesthesia. Preoperative patient factors and treatment outcomes were retrospectively examined according to the sedation method. Results Among patients with ESGC undergoing ESD at our hospital, DEX was more frequently used alongside sedation in men, those undergoing gastrectomy, those with a lesion diameter ≥20 mm, and those with preoperative ulcers. In the standard group, patients whose treatment duration exceeded 120 min typically had a lesion diameter ≥20 mm, preoperative ulcers, lesions located outside the L region, and were treated by junior physicians. Conclusion It is important to evaluate specific preoperative factors (lesion diameter ≥20 mm, preoperative ulcers, lesion located outside the L region, and having a junior physician as the treating physician) in patients undergoing ESD for ESGC to determine whether the combined use of DEX in sedation is necessary.